PARTISIPASI PASANGAN USIA SUBUR DALAM PROGRAM KELUARGA BERENCANA DI KOTA PADANG PANJANG - Ananda, Livia livia; Iskarni, Paus (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This study aims to describe the participation of couples of childbearing age (PUS) in the Family Planning (KB) program in the city of Padang Panjang. This research method is descriptive quantitative method with the analytical technique used is univariate analysis which is calculated the percentage then presented in tabular form and narrated. The sample in this study was 102 fertile age couples in two sub-districts in Padang Panjang City, namely West Padang Panjang District and East Padang Panjang District. The results in this study can be seen that those who participate in the family planning program are 86 people of childbearing age with a percentage of 84.31% and those who do not participate in the family planning program are 16 couples of childbearing age with a percentage of 15.69%. From 86 couples of childbearing age who participated in family planning, it can be seen that those who participated in the Family Planning program to delay pregnancy in Padang Panjang Barat District were 17 couples of childbearing age in West Padang Panjang District and 13 couples of childbearing age in East Padang Panjang District, so that The total number of delayers is 30 couples of childbearing age who are classified as having a participation rate for delaying pregnancy, which is at a low level with a percentage of 34.69% in West Padang Panjang District and 35.14% in East Padang Panjang District. The participation of couples of childbearing age in the family planning program tospace out pregnancies was 32 women of childbearing age in Padang Panjang Barat subdistrict and 24